2017
DOI: 10.3141/2659-23
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Future?: Development and Application of Pedestrian Safety Performance Functions to Prioritize Locations in Seattle, Washington

Abstract: This study aimed to use robust analysis methods to identify and screen locations at risk for pedestrian crashes and injuries to help Seattle, Washington, a Vision Zero city, broaden treatment priorities beyond only high-crash locations. For this objective, data from the entire network were used to develop safety performance functions (SPFs) for two pedestrian crash types: total pedestrian crashes at intersections (a high frequency type) and a subset of intersection crashes involving through motorists striking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…These road safety assessments will help to validate the analysis and to identify any risk factors previously missed. A similar process was undertaken for the intersection study described in Thomas et al ( 14 ); the City identified turning movement conflicts and used the results of their observations and the systemic analysis to inform their long-term funding and treatment plans to implement leading pedestrian intervals at intersections with prior observed crashes, and with higher predicted crashes. At the time of writing, SDOT intends to undertake the same type of verification for the current study and will therefore demonstrate the potential for a systemic approach to prioritizing segment-related systemic projects among possible candidate sites.…”
Section: Application Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These road safety assessments will help to validate the analysis and to identify any risk factors previously missed. A similar process was undertaken for the intersection study described in Thomas et al ( 14 ); the City identified turning movement conflicts and used the results of their observations and the systemic analysis to inform their long-term funding and treatment plans to implement leading pedestrian intervals at intersections with prior observed crashes, and with higher predicted crashes. At the time of writing, SDOT intends to undertake the same type of verification for the current study and will therefore demonstrate the potential for a systemic approach to prioritizing segment-related systemic projects among possible candidate sites.…”
Section: Application Of Resultsmentioning
confidence: 99%
“…Systemic and risk-based analyses, though relatively new in pedestrian safety analysis, have already seen several applications. For example, Thomas et al previously conducted an empirically based systemic safety analysis of intersections in Seattle to identify risk locations for pedestrians ( 14 ). Drawing upon prior risk factor identification and crash analysis, the Arizona Department of Transportation implemented a systemic pedestrian risk program to identify, prioritize, and select sites for treatment through its Arizona Pedestrian Safety Action Plan (PSAP) ( 15 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most common variables in these models represent exposure. Higher pedestrian volumes (22)(23)(24)(25), higher bicyclist volumes (26), and higher motor vehicle volumes (22)(23)(24)26) are typically associated with more crashes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Physical design and other intersection context variables are also included in some models. After controlling for exposure, models have shown positive associations between pedestrian crashes and signalized intersections (23), roadways with more travel lanes (23,27), rightturn-only lanes (22,28), crosswalks at midblock locations (28), on-street parking (23,24), bus stops (23), nearby commercial land uses (22,24,28), adjacent lower-income neighborhoods (23), and urban areas (25). Models have shown negative associations between pedestrian crashes and raised medians (22,25,27), pedestrian hybrid beacons (25), rapid flashing beacons (25), and advance yield or stop treatments (25).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Central reservationsThomas et al[23], Rankavat and Tiwari[25], De Lavalette et al[30], Damsere-Derry et al [34], Zegeer et al [35], Gårder [36] Pedestrian Infrastructure Sidewalk Ding et al [12], Ukkusuri et al [16], Rankavat and Tiwari [Public lighting Mukherjee and Mitra [22], Lee and Abdel-Aty [27], Assum et al [38], Wanvik [39] Traffic Characteristics Pedestrian traffic volume Elvik [8], Miranda-Moreno et al [9], Chen and Zhou [17], Pulugurtha and Sambhara [18], Thomas et al [23], Dumbaugh and Rae [26], Zheng et al [40] Vehicular traffic volume Elvik [8], Miranda-Moreno et al [9], Pulugurtha and Sambhara [18], Wedagama et al [20], Wier et al [21], Thomas et al [23], Rankavat and Tiwari [25], Lee and Abdel-Aty [27], De Lavalette et al [30], Clifton et al [41], Diogenes and Lindau [42], Landis et al [43], Yagil[44] …”
mentioning
confidence: 99%